Programmer Performance Influencing Factors with Sequential Explanatory Model - Siska Restu Anggraeny Iskandar; Sumarsono Sumarsono; Norma Latief Fitriyani; Sendy Aditya Suryana (IJID (International Journal on Informatics for Development), 2018)
Implementation is one of phases in Software Development Life Cycle (SDLC). A programmer is a software development leader decides whether software is completed on time or postpone according to development schedule. Data Warehouse and IT Center (PTIPD) is  a software developer official vendor in UIN Sunan Kalijaga, they developed a growing number of software to facilitate administrative processes in college academic community. This is an analysis to determine the factors that most influence the developers. The object of this research are nine people.  They are all software programmer in PTIPD. The research using Mixed Methods Research that combines two methods of research, qualitative and quantitative. Two factors from previous research are factors materialistic and non-materialistic factors. Materialistic factors are Reward and Punishment; Career Development and Contra-Accomplishment, Incentive and Bonus. Non-Materialistic factors are Usefulness, Relationships and Spirituality. Preliminary data taken from interviews, observation and documentation study to discover object opinions and views. Validity Test and Reliability Test using SPSS software for qualitative data is provided. The most influencing factor for performance of SDLC programmers of PTIPD UIN Sunan Kalijaga is Usefulness with the highest values are on three informants: Oscar, Bravo, and Mike, also Relations with the highest values are on three informant: Delta, Sierra, and Zulu.